Propuesta de reglamento de registro, control sanitario, publicidad y promoción de alimentos en el Ecuador - Samaniego Vélez, Felipe José (2014)
One of the constitutional rights protected in Ecuador, is the availability of goods and services of optimal quality as well as clear and accurate information regarding their class and content. It is imperative that the rules governing the information provided in the food packages and the quality of goods we buy every day in our country are based on laws prepared according to the reality in which manufacturers; authorities, suppliers and consumers are immersed. Among the most important products regulated are medicines and processed food, which must comply with a mandatory regulation of obtaining the Health Registration, which is necessary when manufacturing, importing, exporting and marketing any product in Ecuador. Throughout this investigation we will focus only on processed foods, and the different scenarios in which you can see the actors involved in the production-consumption chain, such as users, authorities and consumers. Through this analysis we seek to establish the necessary guidelines in order to develop a regulation proposal that meets the needs of all those on the production-consumption chain. In order to be able to develop a proposal in accordance with the national situation, we will look at the historical legislation, the legislation in force and the different cases that occur and how the law in enforced and applied to these situations. We seek to develop a proposal in which the outcome is a win-win situation, meeting the needs of the authority, industry, and consumers, therefore obtaining a better product for the final consumer.